Effects of supplementing calcium salts of polyunsaturated fatty acids to late-gestating beef cows on performance and physiological responses of the offspring - Marques, R. S.; Cooke, R. F. [UNESP]; Rodrigues, M. C. [UNESP]; Brandão, A. P. [UNESP]; Schubach, K. M.; Lippolis, K. D.; Moriel, P.; Perry, G. A.; Lock, A.; Bohnert, D. W. (Oxford University Press (OUP), 2017)
This experiment compared performance and physiological responses of the offspring from cows supplemented with Ca salts of PUFA or SFA + MUFA during late gestation. Ninety-six multiparous, nonlactating, pregnant Angus × Hereford cows were ranked by BW, BCS, and age and divided into 24 groups of 4 cows/group at the end of their second trimester of gestation (d −7). Cows conceived during the same estrus synchronization + AI protocol, with semen from a single sire; hence, gestation length was 195 d for all cows at the beginning of the experiment (d 0). Groups were randomly assigned to receive (DM basis) 405 g/cow daily of soybean meal in addition to 1) 190 g/cow daily of Ca salts of PUFA based on eicosapentaenoic, docosahexaenoic, and linoleic acids or 2) 190 g/cow daily of Ca salts of SFA + MUFA based on palmitic and oleic acids (CON). Groups were maintained in 2 pastures (6 groups of each treatment/pasture) and received daily 10.1 kg/cow (DM basis) of grass–alfalfa hay. Groups were segregated into 1 of 12 drylot pens (6 by 18 m) and individually offered treatments 3 times/wk from d 0 until calving. Cow BW and BCS were recorded, and blood samples were collected on d −7 of the experiment and also within 12 h after calving. Calf BW was also recorded within 12 h of calving. Calves were weaned on d 280 of the experiment, preconditioned for 45 d (d 280 to 325), transferred to a growing lot on d 325, and moved to a finishing lot on d 445, where they remained until slaughter. At calving, PUFA-supplemented cows had a greater (P < 0.01) proportion (as % of total plasma fatty acids) of PUFA, including linoleic, linolenic, arachidonic, docosapentaenoic, and docosahexaenoic acids. At weaning, calves from CON-supplemented cows were older (P = 0.03), although no treatment differences were detected (P = 0.82) for calf weaning BW. During both growing and finishing phases, ADG was greater (P ≤ 0.06) in calves from PUFA-supplemented cows. Upon slaughter, HCW and marbling were also greater (P ≤ 0.05) in calves from PUFA-supplemented cows. Collectively, these results indicate that supplementing eicosapentaenoic, docosahexaenoic, and linoleic acids to late-gestating beef cows stimulated programming effects on postnatal offspring growth and carcass quality. Therefore, supplementing late-gestating beef cows with Ca salts of PUFA appears to optimize offspring productivity in beef production systems.
Keywords: Beef cows; Offspring; Polyunsaturated fatty acids; Pregnancy; Supplementation